Fuzzy logic in the problems of determining the economic parameters of project implementation - Matviienko, Olha; Zakutnii, Serhii (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2024)
The goal of this work is to forecast project execution terms and its main economic parameters using graph theory and fuzzy logic methods. The subject of research in the article is the method of calculating the main properties or parameters of the project, forecasting the terms of its implementation and the possibility of taking into account force majeure situations. The article discusses the task of finding the optimal plan for the project of creating an e-commerce site and calculating its main economic parameters. The work uses methods of the theory of network planning and management. Fuzzy logic methods are used to solve the fuzzy optimization problem. Graph theory methods, namely the CPM critical path method, are used to forecast project deadlines. The following results were obtained: the main economic parameters were calculated for two versions of the project to create an e-commerce site – sequential, when the team does not have many developers to implement it (or enough resources), and parallel execution of work, which allows you to optimize the execution time by involving additional workers. The cost of both projects was also calculated, which in the future can help managers draw conclusions regarding the implementation of one or another planning option for this type of project. For the first project, the project work plan will be completed in a time not exceeding 230 days, with a reliability of 30%. Or does not exceed 295 days with a reliability of 80% percent. For the second project, the project work plan will be completed in a time not exceeding 230 days, with a reliability of 30%. Or does not exceed 278 days with a reliability of 70% percent. Conclusions: the paper proposes a fuzzy mathematical model for finding the optimal plan and calculating the main economic parameters of the project of creating an e-commerce site with a fuzzy set of plans and a vaguely defined goal. The work also presents a method for solving this problem. The obtained results of the research are of great value for planning the project, for solving the question of the feasibility of its initiation, for forecasting the resources that will be needed for its implementation. These indicators are essential for improving processes and correct allocation of work, which can help strengthen competitiveness and increase project profits.